Avaliação dos efeitos de 2ª ordem em edifícios de aço utilizando métodos aproximados e análise rigorosa - Renata Gomes Lanna da Silva (2004)
Second-order elastic analysis must be used by engineers for designing and project of structural systems, mainly in those that present considerable horizontal deflections, becoming more significant the second-order effects. The objective of this work consists, therefore, in evaluating the second-order effects in multistory steel plane frames; braced and unbraced, using several approximates second-order analysis. For this, fundamental concepts and an overview of the global behavior of steel plane frames are presented, in order to get a good knowledge of the stability of these structures. After that, approximate second-order methods are presented: the method of the Moments Amplification (B1-B2), the Equivalent or Fictitious Lateral Forces and the ãz Coefficient. These methods are compared to second-order rigorous analysis methods, using the software PPLANLEP for the unbraced frames, based on a consistent theoretical formulation for a non-linear analysis, physical and geometrical, by the finite elements method and, for the braced frames, the software ANSYS 6.1 (2002). Finally, examplesare presented with the purpose to evaluate the consistency and accuracy of the results obtained by the several approximate methods, and to get conclusions of practical character that will be able to serve like suggestions for steel structures design. An estimate analysis, proposal in the base text of review of NBR 8800 (2003), also is presented will the objective to check its usefulness in the structural analysis of steelplane frames.